2012
DOI: 10.12697/akut.2011.17.06
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hip muscle strength after proximal femoral fracture in elderly women

Abstract: Hip muscle weakness is an often-occurring condition after displaced fractures of the proximal femur in older patients. The aim of this study was to compare hip muscle strength and pain in elderly female patients after proximal femoral fracture. Nine female patients (mean±SD of 71.4±3.9 yrs) participated in this study. Knee extensor, hip abductor and adductor muscle strength was evaluated with handheld dynamometer Lafayette (USA) during the first week of postoperative stay in hospital, and 6 months postfracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…N. Ivanova et al found that maximum voluntary isometric force generated in knee and hip muscles for the fractured leg was markedly increased at one week and 6 months postoperatively. 9 In our study we found that two patients (4.4%) had initial abductor power grade 1. 29 patients (64.4%) had grade 2 power and rest had grade 3 muscle power.…”
Section: Discussionmentioning
confidence: 45%
“…N. Ivanova et al found that maximum voluntary isometric force generated in knee and hip muscles for the fractured leg was markedly increased at one week and 6 months postoperatively. 9 In our study we found that two patients (4.4%) had initial abductor power grade 1. 29 patients (64.4%) had grade 2 power and rest had grade 3 muscle power.…”
Section: Discussionmentioning
confidence: 45%
“…Similarly if the entry site is through pyriformis fossa it may disturb the abductor musculature [20] . Rudy Rendle et al found that those implants that require excessive reaming of the greater trochanter to proximal aspect of implant may cause abductor muscle wasting and Trendelenburg gait (10). Many studies have been done in which the PFN has been reinforced with GT fixation devices.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observational studies done by N Ivanova et al [23] In immediate post-operative period modified Mckays criteria is useful to assess the abductor weakness and should be routinely used Strengthening exercises are the key to the functional improvement of patients along with gait or ADL training or proprioception and others like motor stimulation apparatuses and analgesia. Limitations of mobility are quite common and are partially related to the lack of strength and muscle power [24] . The goal of physical therapy in postoperative treatment of patients with a proximal femoral fracture should be to increase muscle strength, and to improve ambulation and efficiency, thus enabling the elderly patient to become independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal femoral fractures (PFFs) frequently occur in the elderly population, 1 which represent a medical and socioeconomic burden, with a reported global annual incidence of approximately 1.3 million. 2 This number is predicted to increase to about 6 million by the year 2050. 3 Using cephalomedullary nails (CMNs) or the so-called proximal femoral nails (PFNs) for treating these fractures became the gold standard approach since its introduction in the 1980s.…”
Section: Introductionmentioning
confidence: 99%